Musculoskeletal Imaging: a core review - Spicer, P. J. Paul J; Beaman, F. Francesca; Blomquist, G. A. Gustav A; Montgomery, J. Justin; Maxwell, M. E. Matthew E (Wolters Kluwer, 2015)
Musculoskeletal Imaging: A Core Review will consist of approximately 300 musculoskeletal radiology questions, in the format similar to the core exam. High quality radiographs, CT, MRI, and ultrasound images will be included. Answers to the questions will be discussed in a concise manner with explanations for why a particular answer choice is correct and the remaining answer choices are incorrect. Literature references will be provided for each answer explanation, so a reader will know where to go for further reading on the subject. This will be the first review book available to radiology residents preparing for the new core exam.